2023
DOI: 10.3389/fgene.2023.1159167
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of NLRP3 inflammasome intervention for synovitis in knee osteoarthritis: A review of TCM intervention

Abstract: Objective: This paper briefly reviews the structure and function of NLRP3 inflammasomes, signaling pathway, relationship with synovitis in KOA, and intervention of traditional Chinese medicine (TCM) in NLRP3 inflammasomes as a means to improve its therapeutic potential and clinical application.Method: Literatures about NLRP3 inflammasomes and synovitis in KOA were reviewed to analyze and discuss.Result: NLRP3 inflammasome can activate NF-κB mediated signal transduction, which in turn causes the expression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that canonical inflammasomes and the NLRP3 inflammasome are actively involved in the pathogenesis of OA and that selective targeting of canonical inflammasomes is an emerging pharmacological strategy for OA therapy [70][71][72][73][74]. Accumulating evidence has revealed that non-canonical inflammasomes are possible players in OA pathogenesis.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…Previous studies have demonstrated that canonical inflammasomes and the NLRP3 inflammasome are actively involved in the pathogenesis of OA and that selective targeting of canonical inflammasomes is an emerging pharmacological strategy for OA therapy [70][71][72][73][74]. Accumulating evidence has revealed that non-canonical inflammasomes are possible players in OA pathogenesis.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…In recent years, the research in the field of KOA has been increasingly in-depth. Current studies focus on cytokines, particularly those crucial to inflammation (12,13), as well as the mechanisms of gene expression (14,15) and signal transduction pathways (16)(17)(18). The TNF family and MMP enzyme series have been frequently reported to be associated with KOA (13, [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%